2006
DOI: 10.1038/nm1439
|View full text |Cite
|
Sign up to set email alerts
|

rAAV6-microdystrophin preserves muscle function and extends lifespan in severely dystrophic mice

Abstract: Mice carrying mutations in both the dystrophin and utrophin genes die prematurely as a consequence of severe muscular dystrophy. Here, we demonstrate that intravascular administration of recombinant adeno-associated viral (rAAV) vectors carrying a microdystrophin gene restores dystrophin expression in the striated musculature of these animals, considerably reducing skeletal muscle pathology and extending lifespan. These findings suggest rAAV vectormediated systemic gene transfer may be useful for treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
261
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(266 citation statements)
references
References 15 publications
4
261
1
Order By: Relevance
“…AAV vectors carried mini-or micro-dystrophins (i.e., different reduced parts of the DMD gene that still result in functional forms of the protein) have been used to treat animal models of DMD and DMD patients [19,27]. AAV vectors carrying minigenes have been injected in mdx mice and GRMD dogs demonstrating the efficient therapeutic effects of this treatment [28][29][30]. However, a phase I clinical trial using AAV-mini-dystrophin revealed only limited dystrophin expression and irrelevant muscle improvements due to the potential presence of AAV-neutralizing antibodies already present in humans, and the immune response against non-self-dystrophin [31], which requires this kind of approach be accompanied by immunosuppressive therapy.…”
Section: Gene Therapymentioning
confidence: 99%
“…AAV vectors carried mini-or micro-dystrophins (i.e., different reduced parts of the DMD gene that still result in functional forms of the protein) have been used to treat animal models of DMD and DMD patients [19,27]. AAV vectors carrying minigenes have been injected in mdx mice and GRMD dogs demonstrating the efficient therapeutic effects of this treatment [28][29][30]. However, a phase I clinical trial using AAV-mini-dystrophin revealed only limited dystrophin expression and irrelevant muscle improvements due to the potential presence of AAV-neutralizing antibodies already present in humans, and the immune response against non-self-dystrophin [31], which requires this kind of approach be accompanied by immunosuppressive therapy.…”
Section: Gene Therapymentioning
confidence: 99%
“…10,11 We and others have reported successful improvement of the dystrophic phenotype in skeletal muscles of DMD mice models following introduction of this transgene. 12,13 To achieve transduction of an entire extremity, a limb perfusion by retrograde intravenous administration of the rAAV in larger animal models is being developed. 14 For cardiac transduction, we utilized rAAV serotype 9, which can be administered systemically with excellent cardiac tropism.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of internally truncated dystrophins lacking an appreciable portion of the rod domain has also been demonstrated in transgenic mdx mice, and exploited to design so-called microdystrophins compatible with delivery by AAV vectors. These engineered recombinant microdystrophins have been shown to restore normal expression of the dystrophin-associated protein complex (DPC), improve sarcolemmal stability, and prevent myofiber degeneration in the mdx mouse model (Wang et al, 2000;Fabb et al, 2002;Harper et al, 2002;Gregorevic et al, 2006).…”
Section: Introduction Dmentioning
confidence: 99%